Groundless Metaphors and Living Maps in the Writing of Mary Shelley - McEvoy, Emma (Romanticism on the Net, 2005)
AbstractIn this article I consider Mary Shelley’s use of figuration, examining its characteristic forms. In three main sections address her use of allegory, what I call the “infection of the metaphorical”, and the groundless metaphor. Shelley’s writing will be looked at in dialogic relation to her predecessors and contemporaries and her peculiar stylistics discussed in terms of her sceptical attitude toward, and undermining of Romantic idealism. There will be specific emphasis on her treatment of favourite Romantic projects - nature, writing the self and the perceiving mind. Shelley will be discussed both as revisionist and saboteuse in her attitude to language.